2014
DOI: 10.1021/jf5044426
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Byproducts Originating from Hemp Oil Processing

Abstract: Valorization of hemp seed meal, a byproduct of hemp oil processing, was performed by measuring the distribution of nutritional and antinutritional compounds in different hemp seed meal fractions. According to chemical composition, two cotyledon-containing fractions (>180 and <180 μm) were significantly richer in protein (p < 0.05) (41.2% ± 0.04% and 44.4% ± 0.02%, respectively), lipid (15.1% ± 0.02% and 18.6% ± 0.04%, respectively), and sugar content (4.96% ± 0.11% and 3.46% ± 0.08%, respectively) in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 39 publications
8
85
2
5
Order By: Relevance
“…After the defatting step, protein levels rose significantly, increasing by 15.6% for safflower (92.9%, db), 8% for sunflower (75.5% db), 8% for canola (66.0% db), and 12% for hemp (83.2% db) ( Table 1). The hemp protein concentrates in this study also had higher L* values than what has been reported for fractions from pressed hemp meal (Pojic et al, 2014), a defatted hemp seed cake and acid and alkali extracted protein isolates (Teh et al, 2014). Protein levels in the oilseed concentrates were similar to the commercial ingredients of faba bean, lentil, soy, and whey, which ranged from 63.4% to 78.5% (db), but higher than the great northern bean and pea protein concentrates (~46%).…”
Section: Physicochemical Propertiessupporting
confidence: 50%
“…After the defatting step, protein levels rose significantly, increasing by 15.6% for safflower (92.9%, db), 8% for sunflower (75.5% db), 8% for canola (66.0% db), and 12% for hemp (83.2% db) ( Table 1). The hemp protein concentrates in this study also had higher L* values than what has been reported for fractions from pressed hemp meal (Pojic et al, 2014), a defatted hemp seed cake and acid and alkali extracted protein isolates (Teh et al, 2014). Protein levels in the oilseed concentrates were similar to the commercial ingredients of faba bean, lentil, soy, and whey, which ranged from 63.4% to 78.5% (db), but higher than the great northern bean and pea protein concentrates (~46%).…”
Section: Physicochemical Propertiessupporting
confidence: 50%
“…Differences in the chemical composition of untreated cakes, cakes before and after treatment, as well as cakes treated with T. versicolor and H. grisea were analyzed for significance using the analysis of variance (ANOVA). Regarding hemp seed oil cake, all values reported in the literature [39][40][41] were higher than the value determined in this paper (24.77 ± 0.41% db), except for those published by Cozea et al [12], where the content of total proteins was 24.86%. [14].…”
Section: Resultscontrasting
confidence: 82%
“…Ether extract content in hemp seed oil cake (12.34% db) differs to some extent from the results found in the literature (5.18-11.9% db) [12,[39][40][41]. Ether extract content in hemp seed oil cake (12.34% db) differs to some extent from the results found in the literature (5.18-11.9% db) [12,[39][40][41].…”
Section: Resultsmentioning
confidence: 66%
“…Regardless of their detrimental effect, antinutritional compounds can also exhibit health‐promoting features in terms of prevention of diabetes, cancer and cardiovascular diseases (Pojić et al . ).…”
Section: Resultsmentioning
confidence: 97%